Accurate energy‐size dependence of excitonic transitions in semiconductor nanocrystals and nanoplatelets using a phase jump approach. Issue 3 (19th December 2013) - Dijksman, Arjen T.; Dubertret, Benoit
<x xml:space="preserve">Abstract</x> Accurate energy‐size dependence of excitonic transitions in semiconductor nanocrystals in the strong confinement regime using classical theoretical approaches such as effective mass (EM) approximation, tight binding (TB), or empirical pseudo‐potential is difficult. We propose a simple empirical expression with three fitting parameters that accurately relates the size dependence of most known excitonic transitions in CdSe and in InAs nanocrystals. We show that this empirical expression can be deduced from a phase jump approach if the charge carriers are considered to travel on the atomic lattice of the nanocrystal and gain energy upon bouncing at the nanoparticle boundaries. This empirical expression is also tested on the atomically flat CdSe nanoplatelets (NPLs) without any adjustment of the parameters obtained with the CdSe spherical nanocrystals, and provides an estimation of the CdSe NPLs thickness that matches exactly the experimental observations. These results suggest that a phase shift approach could be useful to describe the electronic transitions in semiconductor nanocrystals.